Hydrodynamic Analysis-Based Modeling of Coastal Abrasion Prevention (Case Study: Pulau Baai Port, Bengkulu) - Mudji Irmawan; Muhammad Hafiizh Imaaduddiin; Rizki Robbi Rahman Alam; Afif Navir Refani; Anissa Nur Aini (Applied Sciences, 2024)
Pulau Baai Port, located strategically in the Indian Ocean and considered a vital maritime hub in Indonesia, grapples with persistent challenges related to abrasion and sedimentation, which negatively impact its maritime infrastructure. One of the affected components is the exposed gas pipeline installation along the port’s coastline. The sedimentation rate along Pulau Baai’s coastline is alarming, ranging from 600,000 to 800,000 m3/year, resulting in coastal abrasion at a rate of up to 20 m/year. This study focuses on three scenarios using MIKE 21, including a baseline without alternatives, shore protection alternatives, and jetty protection alternatives. A comprehensive dataset, incorporating bathymetric maps, wave patterns, current data, and sediment characteristics, supports the analysis of coastal dynamics, emphasizing the urgency for intervention. The research introduces the novelty of analyzing coastal abrasion through the exposure of underground pipelines, establishing a relationship between impacting factors such as wave height, tides, sedimentation, and coastal abrasion. Mitigation alternatives, particularly alternative model-2 with jetty protection, are recommended based on a thorough evaluation of the model performance and actual measurements. The results show that Pulau Baai’s sediment, primarily sandy, experiences substantial abrasion and coastline changes, notably in alternatives-2 and -3. The study anticipates potential sedimentation in certain sections of the subsea exposed pipelines in the absence of shore protection. The outcomes of this research provide a foundational guide for informed decision making and strategies to ensure the sustainable functionality of maritime infrastructure in Pulau Baai and similar coastal regions.